Assessment of hazardous substances in the snail, Nerita lineata gmelin, and sediments from selected mangrove areas of Peninsular Malaysia - Cheng, Wan Hee (2015)
Rapid growth of the land and marine based industries has generated various contaminations to the coastal areas of Malaysia. Thus, continuous assessments and monitoring of pollutants especially trace metals and polycyclic aromatic hydrocarbons (PAHs) are crucial. The aim of this study is to determine the baseline data, ecological risk and health risk assessments of trace metals and PAHs in mangrove snails, Nerita lineata and surface sediments of at least 9 sampling sites in Peninsular Malaysia between 2010 − 2012. Metal analysis was done by using the Atomic Absorption Spectrophotometer (AAS) and Inductively Coupled Plasma-mass Spectrometer (ICPMS). Analysis of PAHs was carried out by using gas chromatography-mass spectrophotometry (GC-MS) while Inter-Simple Sequence Repeat (ISSR) markers were applied for genetic polymorphism study in the snails. All 18 metals in the snails ranged from BDL (below detection limit) – 3235 µg/g dw, with higher accumulation of essential metals in the soft tissues and non-essential metals in the shells and opercula. For sediments, all 18 metals ranged from 0.003 – 48916 µg/g dw. The ∑16 PAHs concentrations (ng/g dw) ranged from 871 – 3066 and 273 – 18030 for soft tissues and sediments, respectively. To determine the ecological risks of habitat on surface sediments, the sediment quality guidelines (SQGs), geochemical indices, potential ecological risk index (PERI) and mean ERM quotient (m-ERM-q) were used. Based on the SQGs, all the metals investigated were unlikely to cause any adverse ecological effects. The ecological risk indices revealed that the pollution and ecological risks of all metals and PAHs were minimal, except for PAHs in JPKetam being ‘moderately to highly polluted’. Potential health risks were assessed from calculations of estimated daily intakes (EDI), target hazard quotients (THQ) and total THQ (TTHQ) of the snails’ soft tissues for trace metals, while excess cancer risks (ECR) were applied for PAHs assessments. Non-carcinogenic risks estimation (THQ and TTHQ) for trace metals showed that average snails consumers were exposed to low potential health risk whereas the high consumers were at high risks (TTHQ>1). The carcinogenic risks approach (ECR) showed that the snail consumption from most sites were in a range of moderate to high carcinogenic risks exposure (1×10-6 < ECR< 1×10-4 ) to PAHs, implying moderation (<17.86 g/day) in snail consumption. The ISSR markers were found to have positive relationships from comparison of patterns of genetic clustering and trace metal levels of the snail muscle tissues but not PAHs. This implied that the polymorphic loci could be used as potential biomarkers for metals pollution. Generally this study suggested that all metals and PAHs from the sampling sites were not likely to cause hazardous effects to the environment. Consumption of the snails should be of moderation especially to high consumers of the snails as the data showed possible health risks for both trace metals and PAHs. This study has produced important data of the hazardous pollutants in the snails and sediments which can be used for environmental management in future.